2020
DOI: 10.1136/practneurol-2020-002633
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia and neuromuscular disorders: what a neurologist needs to know

Abstract: Neurologists are often asked for specific advice regarding patients with neuromuscular disease who require general anaesthesia. However, guidelines on specific neuromuscular disorders do not usually include specific guidelines or pragmatic advice regarding (regional and/or general) anaesthesia or procedural sedation. Furthermore, the medical literature on this subject is mostly limited to publications in anaesthesiology journals. We therefore summarise general recommendations and specific advice for anaesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…MG patients are potentially more sensitive to sedatives and anesthetics [ 120 ]. For example, use of benzodiazepines in MG patients who have significant bulbar symptoms or borderline respiratory reserve could result in respiratory insufficiency by causing a central respiratory depression and obstruction of the upper airways [ 120 ]. High doses of benzodiazepines should preferably be avoided or be used with close monitoring of the respiratory status such as respiratory rate and pulse oximetry.…”
Section: Drugs That Worsen Mg or Cause Mg-like Symptoms Through DImentioning
confidence: 99%
See 4 more Smart Citations
“…MG patients are potentially more sensitive to sedatives and anesthetics [ 120 ]. For example, use of benzodiazepines in MG patients who have significant bulbar symptoms or borderline respiratory reserve could result in respiratory insufficiency by causing a central respiratory depression and obstruction of the upper airways [ 120 ]. High doses of benzodiazepines should preferably be avoided or be used with close monitoring of the respiratory status such as respiratory rate and pulse oximetry.…”
Section: Drugs That Worsen Mg or Cause Mg-like Symptoms Through DImentioning
confidence: 99%
“…There is subsequent muscle relaxation as AChR becomes insensitive to ACh. The action of succinylcholine is not reversed by ACh esterase inhibitors and even enhanced by those medications [ 120 ]. In 1953, Anderson et al reported prolonged apnea after use of succinylcholine to remove bronchial tumor in a patient with myasthenia, in retrospect a likely Lambert–Eaton syndrome [ 125 ].…”
Section: Drugs That Worsen Mg or Cause Mg-like Symptoms Through DImentioning
confidence: 99%
See 3 more Smart Citations